Awareness and attitude towards corporate social responsibility: A study of MBA students in Rajasthan. Issue 3 (6th May 2014) - Jain, Priyanka; Kumar Datta, Saroj; Roy, Ankur
Abstract : Purpose: – This paper is an attempt to explore the awareness and attitude of the management students towards corporate social responsibility (CSR). Students are perceived as future managers of the corporate world and their perception about CSR is deemed important to business organisations. The students can make companies understand their responsibility towards various stakeholders. The paper aims to discuss these issues. Design/methodology/approach: – By doing a review of past literature, an appropriate scale consisting of forty-one items has been developed to measure the dimensions of CSR. Data were collected from 294 students of various business schools situated in Rajasthan (India). The data collected was subjected to exploratory factor analysis to extract the main dimensions that would bring out the attitudes of the students towards CSR. Findings: – Results revealed that the companies should pay attention to accountability towards stakeholders, corporate governance, ethical commitment and humanitarian concerns besides fulfilling other responsibilities as covered under the eight factors identified in the study. Research limitations/implications: – This paper used survey data from small sample of management students in a limited geographic area. Hence, it might be difficult to generalize the results to a larger, more representative population. The research also suggests how corporations can make CSR an integral part of the business organisation. Practical implications: – The dimensions identified in the study if incorporated by the business in its day-to-day operations can make it socially responsible as well as socially acceptable in the true sense. Originality/value: – This research makes an empirical contribution to identify the factors which management students expect business enterprises should do to be justified as socially responsible corporate citizens.